Solve the factored quadratic equation 0=−1/3x(x−6).(1 point)

1 answer

To solve the factored quadratic equation \(0 = -\frac{1}{3}x(x - 6)\), we will set each factor equal to zero.

The equation can be rewritten as:

\(-\frac{1}{3}x = 0\) or \(x - 6 = 0\).

Now, solve each equation:

  1. From \(-\frac{1}{3}x = 0\):

    • Multiply both sides by -3: \[ x = 0 \]
  2. From \(x - 6 = 0\):

    • Add 6 to both sides: \[ x = 6 \]

Thus, the solutions to the equation are:

\[ x = 0 \quad \text{and} \quad x = 6. \]

So, the final answer is \(x = 0\) and \(x = 6\).